a = (3√-18)^3
a = (3√-1*2*9)^3
a = (3√-1*3^2)^3
a = 3^3√-1*3^2
a = 27√-1*9
a = 27i√9
a = 27i*3
a = 81i
Therefore, A = 81i.
Solve for A. Express your answer in simplest radical form, if necessary.
a=(3√-18)^3
5 answers
In simplest form
A = 81i
Your wrong
Let's reevaluate the problem:
a = (3√-18)^3
a = (3√-1*2*9)^3
a = (3√-1*3^2)^3
a = (3√-1*3^2)^3
a = (3√-1)(3√9)^3
a = (3i)(3)(3)
a = 27i
Therefore, A = 27i in simplest form. Thank you for bringing that to my attention.
a = (3√-18)^3
a = (3√-1*2*9)^3
a = (3√-1*3^2)^3
a = (3√-1*3^2)^3
a = (3√-1)(3√9)^3
a = (3i)(3)(3)
a = 27i
Therefore, A = 27i in simplest form. Thank you for bringing that to my attention.